Anterograde Amnesia as a Manifestation of Acute Type A Aortic Dissection - Stöllberger, Claudia; Koller, Julia; Finsterer, Josef; Schauer, Dominic; Ehrlich, Marek (International Journal of Angiology, 2019)
Objectives Memory impairment has been only rarely reported in association with acute aortic dissection type A. We report a patient with pure anterograde amnesia and memory impairment of contents occurring after the event, accompanying acute aortic dissection type A.Case Report A previously healthy 53-year-old Caucasian male was admitted because of sudden chest pain after having lifted a heavy object. Clinical examination and electrocardiogram showed no abnormalities. Since blood tests showed leukocytosis, anemia, and elevated D-dimer level, either pulmonary embolism or aortic dissection was suspected; therefore, computed tomography was suggested. The patient seemed disoriented to time, and neurologic investigation confirmed that the patient was disoriented to time; short time memory was severely impaired and concentration was reduced. An amnestic episode with anterograde amnesia was diagnosed. Computed tomography showed type A aortic dissection. A supracoronary replacement of the ascending aorta was performed. The patient was discharged on the 7th postoperative day. Three months postoperatively, the patient is clinically stable; however, amnesia for the interval between pain onset and cardiac surgery persists.Conclusions Transient amnesia, usually considered a benign syndrome, may be more common than generally recognized in aortic dissection. The suspicion for aortic dissection or other cardiovascular emergencies is substantiated when amnesia is associated with sudden onset of chest pain, leukocytosis, and elevated D-dimer levels. Computed tomography of the aorta with contrast medium is the imaging method of choice to confirm or exclude the diagnosis.
Keywords: aortic dissection; transient global amnesia; chest pain